The THE CORRELATION OF TEACHING BEHAVIOR AND EDUCATIONAL COMPETENCE OF PUBLIC ELEMENTARY SCHOOL TEACHERS - Seraspe, Khent Ryan (IJBLE Scientific Publications Community Inc., 2022)
This study determined the correlation of teaching behavior and instructional competence of public elementary school teachers in the District of Talisayan, Division of Misamis Oriental during the school year 2020-2021. It focused on the different areas of teaching behavior namely: instructional, socio-emotional, and organizational. Instructional competence focused on different domains such as: mastery of the subject matter, teachings skills, classroom management, and evaluation skills. The relationship of the abovementioned dimensions were also determined as to the public school teachers’ teaching performance. This study used the descriptive correlational method of research and data were analyzed using mean, standard deviation, and Pearson-r moment correlation. The participants of the study were the 89 randomly chosen public school teachers of Talisayan District. The research instrument used to conduct the study on the aspect of teaching behavior was adopted from Connor et al. (2009); while the instructional competence facet was adopted from Barnuevo et al. (2012). Generally, the public elementary school teachers Always exhibit all the dimensions of teaching behaviors. Further, their level of instructional competence is very high. In general, there was a significant relationship between the teaching behavior and instructional competence of the teachers. However, among the dimensions, it was specifically revealed that there was a high significant relationship between organizational teaching behavior and evaluation skills.